Respuesta :
Answer:
x=-8
Step-by-step explanation:
-8x - 8 + 3(x-2) = -3x + 2 Multiply the parentheses by 3
-8x - 8 + 3x -6= -3x +2 Collect all like terms and Calculate
-5x - 14= -3x + 2 Move the terms
-5x + 3x = 2 + 14 Collect all the like terms and Calculate the sum
-2x = 16 Divide both of the sides by -2
x = -8
I hope this is what you were looking for and helps you out.
Answer:
[tex]x=-8[/tex]
Step-by-step explanation:
Given Equation:
[tex]-8x-8+3(x-2)=-3x+2[/tex]
Solving for 'x' by taking the terms of 'x' to one side and constants to the other side:
[tex]-8x-8+3(x)-3(2)=-3x+2\\[/tex]
[tex]-8x-8+3x-6=-3x+2[/tex]
Adding the like terms:
[tex]-5x-14=-3x+2[/tex]
Adding '[tex]3x[/tex]' both sides:
[tex]-5x+3x-14=-3x+3x+2[/tex]
[tex]-5x+3x-14=2\\\\-2x-14=2[/tex]
Adding '[tex]14[/tex]' both sides:
[tex]-2x-14+14=2+14\\\\-2x=16\\\\x=\frac{16}{-2}[/tex]
[tex]x=-8[/tex]